2017
DOI: 10.1016/j.ctrv.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A review on the evolution of PD-1/PD-L1 immunotherapy for bladder cancer: The future is now

Abstract: The treatment of bladder cancer has evolved over time to encompass not only the traditional modalities of chemotherapy and surgery, but has been particularly impacted by the use of immunotherapy. The first immunotherapy was the live, attenuated bacterial Bacillus Calmette-Guérin vaccine, which has been the standard of care non-muscle-invasive bladder cancer since 1990. Modern immunotherapy has focused on inhibitors of checkpoint proteins, which are molecules that impede immune function, thereby allowing tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
231
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(245 citation statements)
references
References 63 publications
2
231
0
4
Order By: Relevance
“…Programmed death ligand 1 (PD‐L1) is a transmembrane protein expressed on immune cells (IC) and tumour cells (TC), whereas programmed cell death (PD)‐1 is expressed on IC and its expression can be induced following T cell activation. Upon binding to the receptor PD‐1 in IC, the overexpressed PD‐L1 in TC leads to functional inactivation of T cells and down‐regulation of T cell antitumoral activity, resulting in immune evasion . In recent years, PD‐L1 and PD‐1 have emerged as a key check‐point that can be manipulated with inhibitory monoclonal antibodies in various cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Programmed death ligand 1 (PD‐L1) is a transmembrane protein expressed on immune cells (IC) and tumour cells (TC), whereas programmed cell death (PD)‐1 is expressed on IC and its expression can be induced following T cell activation. Upon binding to the receptor PD‐1 in IC, the overexpressed PD‐L1 in TC leads to functional inactivation of T cells and down‐regulation of T cell antitumoral activity, resulting in immune evasion . In recent years, PD‐L1 and PD‐1 have emerged as a key check‐point that can be manipulated with inhibitory monoclonal antibodies in various cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several reports that paclitaxel-based chemotherapy has had some effectiveness in terms of improvement of quality of life and prognosis in patients with cisplatin-resistant UC (18,23). In recent years, immune-checkpoint inhibitors have been reported as a novel treatment modality for patients with advanced UC, including platinum-treated advanced UC (21,22). Many investigators and urologists have a great hope of increasing survival with these new agents in patients with advanced and cisplatinresistant UC; however, more careful evaluation of costeffectiveness, useful biomarkers, and safety are essential for standardization (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although no second-line regimen for cisplatin-resistant UC hast yet been established, several clinical studies have demonstrated that paclitaxel-based chemotherapy is useful for improving the quality of life and prognosis in patients with cisplatin-resistant UC (18)(19)(20). In recent years, the efficacy of immune-checkpoint inhibitors was reported in patients with advanced UC (21,22). There is general agreement that this new tool is an epoch-changing therapeutic strategy for these patients.…”
Section: Abstract Background/aim: Class III Beta-tubulin (Tubb3) Expmentioning
confidence: 99%
“…Some studies have reported the therapeutic efficacy of anti‐PD‐1 monotherapy against BCa in mouse models . However, PD‐1 blockade alone has no significant antitumor effect, likely because PD‐1 pathway blockade does not induce a sufficiently strong antitumor response to delay BCa growth . In addition, anti‐PD‐1 monotherapy increased the percentage of CD4 + Foxp3 + T‐cells.…”
Section: Discussionmentioning
confidence: 99%